Impact of glucagon-like peptide 1 analogs on cognitive function among patients with type 2 diabetes mellitus: A systematic review and meta−analysis - Luan, Sisi; Cheng, Wenke; Wang, Chenglong; Gong, Jianhong; Zhou, Jianbo (Frontiers in Endocrinology, 2022)
Background: Diabetes is an independent risk factor for cognitive impairment. However, little is known about the neuroprotective effects of glucagon-like peptide 1 (GLP-1) analogs on type 2 diabetes mellitus (T2DM). Herein, we assessed the impact of GLP-1 analogs on the general cognitive functioning among patients with T2DM. Methods: Relevant studies were retrieved from PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), and ClinicalTrials.gov databases from their inception till June 30, 2022, without any language restrictions. For continuous variables, the mean and standard deviation (SD) were extracted. Considering the heterogeneity in general cognitive functioning assessments among the pooled studies, the standardized mean differences (SMDs) with corresponding 95% confidence intervals (CIs), were calculated. Results: Five studies including 7,732 individuals with T2DM were selected for the meta-analysis. The use of GLP-1 analogs exerted no significant effects on the general cognitive functioning in self-controlled studies (SMD 0.33, 95% CI -0.03 to 0.69). Subgroup analyses among the self-controlled studies based on age and history of cardio-cerebrovascular disease showed that GLP-1 analogs significantly improved the general cognitive functioning in T2DM patients younger than 65 years (SMD 0.69, 95% CI 0.31 to 1.08) or those without cardio-cerebrovascular diseases (SMD 0.69, 95% CI 0.31 to 1.08). Similarly, differences in the general cognitive functioning for GLP-1 analogs between treated and non-treated patients with T2DM were significant in subgroups with patients younger than 65 years (SMD 1.04, 95% CI 0.61 to 1.47) or those with no history of cardio-cerebrovascular diseases (SMD 1.04, 95% CI 0.61 to 1.47). Conclusion: Limited evidence suggests that the use of GLP-1 analogs exerts no significant effects on general cognitive functioning but may be beneficial for patients with T2DM younger than 65 years or those without a history of cardio-cerebrovascular diseases. Further prospective clinical studies with large sample sizes are needed to validate these findings.